The environment as our natural heritage: issues and challenges for sustainable development in Malaysia - Jamaluddin Md. Jahi (Environmental Management Society, Malaysia, 2011)
There is nothine more natural as aheritage than the natural physical environment.The air,water,flora and founa and the land and soil are all the important components of the natural physicalenvironment.They are the natural heritage that has been handed down to us by our ancestors and the same will be handed down to the present and future generations. However , human beings in their quest for the better standard of living and quality of live have often forgotten that their utilisation of the physical environment also leads to environmental degradation. A number of issues related to environmental degradation can be traced even as far back as the beginning of rapid growth of human population and their activities. Human habitat development from mere simple dwellings to present mega cities have impacted on and transformed the natural physical environment and threatening not only our natural heritage, but also human security . Such a situation certainly poses an added challenge on how to manage our environment in a sustainable. This article deals with there main aspects namelay the natural physical environment as a heritage; various issues resulting from human utilisation of the physical environment; and challenges for sustainable development this country.